Eteplirsen for the treatment of Duchenne muscular dystrophy. Issue 5 (10th September 2013) - Mendell, Jerry R.; Rodino‐Klapac, Louise R.; Sahenk, Zarife; Roush, Kandice; Bird, Loren; Lowes, Linda P.; Alfano, Lindsay; Gomez, Ann Maria; Lewis, Sarah; Kota, Janaiah; Malik, Vinod; Shontz, Kim; et al.
<x xml:space="preserve">Abstract</x> Objective In prior open‐label studies, eteplirsen, a phosphorodiamidate morpholino oligomer, enabled dystrophin production in Duchenne muscular dystrophy (DMD) with genetic mutations amenable to skipping exon 51. The present study used a double‐blind placebo‐controlled protocol to test eteplirsen's ability to induce dystrophin production and improve distance walked on the 6‐minute walk test (6MWT). Methods DMD boys aged 7 to 13 years, with confirmed deletions correctable by skipping exon 51 and ability to walk 200 to 400 m on 6 MWT, were randomized to weekly intravenous infusions of 30 or 50 mg/kg/wk eteplirsen or placebo for 24 weeks (n = 4/group). Placebo patients switched to 30 or 50 mg/kg eteplirsen (n = 2/group) at week 25; treatment was open label thereafter. All patients had muscle biopsies at baseline and week 48. Efficacy included dystrophin‐positive fibers and distance walked on the 6MWT. Results At week 24, the 30 mg/kg eteplirsen patients were biopsied, and percentage of dystrophin‐positive fibers was increased to 23% of normal; no increases were detected in placebo‐treated patients (p ≤ 0.002). Even greater increases occurred at week 48 (52% and 43% in the 30 and 50 mg/kg cohorts, respectively), suggesting that dystrophin increases with longer treatment. Restoration of functional dystrophin was confirmed by detection of sarcoglycans and neuronal nitric oxide synthase at the sarcolemma. Ambulation‐evaluable eteplirsen‐treated patients experienced a 67.3 m benefit compared to placebo/delayed patients (p ≤ 0.001). Interpretation Eteplirsen restored dystrophin in the 30 and 50 mg/kg/wk cohorts, and in subsequently treated, placebo‐controlled subjects. Duration, more than dose, accounted for dystrophin production, also resulting in ambulation stability. No severe adverse events were encountered. Ann Neurol 2013;74:637–647